Metodologia para análise técnica e econômica para atendimento de consumidores rurais incluindo GD - Sauer, Eduardo Possebon (2017)
This work presents a methodology for technical and economic analysis for the attendance of residential loads, with different demands and located in the rural area, with the use of distributed generation sources that can work isolated, connected, or even in a mixed way, with the conventional electric power grid, in other words, partially isolated and partially connected to the power network. Through the methodology, it is possible to reduce generation costs and define the best network topology, as well as the positioning of distributed generation sources. The methodology consists of using the data related to the distributed generation sources and the data related to the distribution network, in order to find the minimum net present value between the sources and the optimal network topology. Different sources of distributed generation will be evaluated in three different scenarios, to be then calculated the generation source to be used among the analyzed ones and for the best possible configuration to be found. The solutions demonstrate that just as the type of land affects decisions, the type of energy source also affects, since its current costs in R$/kWh still differ greatly from one to another. In areas with major impediments, such as rivers and forests, transmission networks tend to suffer drift, since it directly affects the cost. Finally, several aspects are important in a study involving sources of distributed generation, since in a rural area, we find from rivers and hills interfering in the construction of transmission networks, as large pasture fields present themselves to facilitate the construction of their own. Thus, through the methodology employed, the final result is the best network configuration and the best selection of energy source to attend the loads.